Tolerance to water deficit in young trees of jackfruit and sugar apple - Rodrigues, Bruno; Souza, Bruna; Nogueira, Rejane; Santos, Mauro (Revista Ciência Agronômica, 2010)
The predawn leaf water potential (Yl), stomatal conductance (gs), CO2 assimilation (A), transpiration (E), chlorophyll a fluorescence and leaf metabolite contents (soluble sugars, proteins and free amino acids) of two tropical fruit species grown in a greenhouse were evaluated to determine the effect of induced water stress on young plants. Six month-old jackfruit (Artocarpus heterophyllus Lam.) and sugar apple (Annona squamosa L.) plants were evaluated in 10.0 L pots after eight days of water withholding, imposed by suspension of irrigation. Jackfruit water status was better than sugar apple. Sugar apple plants showed different daily stomatal behavior when well hydrated, compared to jackfruit plants under the same conditions. The gas exchange of both species showed sensibility to high vapor pressure deficit (VPD). However, under water deficit, photochemical efficiency dropped at midday in both treatments (control and water deficit) and both species showed low tolerance to high VPD and light intensity under greenhouse conditions. In contrast, some chlorophyll fluorescence variables showed good photosystem II stability at highest VPD hour (14:00 h). The present results involving carbohydrate metabolic changes revealed an accumulation of soluble sugars; moreover, protein and free amino acid contents in water stressed leaves also increased. These findings suggest an absence of damage to photosynthetic machinery for water deficit period. Jackfruit revealed greater tolerance to water deficit than sugar apple an important feature for commercial crops in northeastern Brazil.